Stackelberg Security Games for Information Security Management of Financial Systems - Abrahamyan, Ashot A. (Mathematical Problems of Computer Science, 2021)
Information security has become a very important issue as organizations are increasingly becoming dependent on data and information technology for conducting their operation. There are several risks associated with information systems and well-developed models are needed to address those risks. Information systems are constantly being attacked by several actors, including, organized crime, political groups, and intelligence agencies. Organizations continue to invest resources to protect their assets. Both the attackers and defenders have clear motives and gains from their activities. Game theoretic concepts provide an ideal framework to model defender- attacker interactions, particularly Stackelberg Security Games. This paper is focused on application of Stackelberg model to information security management of financial systems.